Автоматизация средств контроля технологического процесса изготовления интегральных схем - Патров, Д. О.; Карнаушенко, В. П. (ХНУРЕ, 2018)
The automation of the means of control of the technological process of manufacturing of integrated circuits allows to measurement of the parameters of integrated circuits (thickness of thin films, their structural homogeneity) with high precision and also considerably reduces influence of a human factor on technological process.
Keywords: Автоматизация средств контроля; Интегральные схемы